The limits of information? A game theoretic contribution to understanding the development of an indicators policy for the UK construction industry - John Rigby; Paul Dewick; Roger Courtney; Sally Gee (The University of Manchester, Manchester Business School, 2011)
In the UK over the last decade, benchmarking has been consistently promoted as a solution to the problems of industry and the construction industry in particular. Government support of benchmarking in construction through the development of a key performance indicators programme found justification in the public goods aspects of the innovation process and because of the presence of market failures of information facing construction clients. However, attempts to merge benchmarking approaches into a single framework did not lead to a combined programme as intended. A game theoretic analysis of the implementation of government policy is presented to account for difficulties encountered by policy actors and to explain why a suitable mechanism to facilitate mutual benchmarking could not be devised. A key performance indicator (KPI) system that supports clients and suppliers in any sector - here we consider construction - is highly problematic, not only because the types of information and types of processes that generate the information used by clients and suppliers are generally different, but because the exchange of information between suppliers and clients and vice versa potentially leads to loss of commercially valuable information.
Keywords: 330; benchmarking; game theory; policy implementation.